ANALISIS GAYA BAHASA PADA ANTOLOGI PUISI 99 UNTUK TUHANKU DAN PEMANFAATANNYA SEBAGAI MEDIA PEMBELAJARAN - Riyan Munajat; Andrie Chaerul; Imam Muhtarom (Program Studi Pendidikan Bahasa Indonesia, STKIP Bina Bangsa Getsempena, 2022)
The background of this research is the fact that language style learning is very important because in addition to helping students to be skilled in language, it can also help students understand literary works. The purpose of this study is to (1) describe the style of language in the poetry anthology “99 for my Lord” by Emha Ainun Nadjib. (2) describe the use of the results of the analysis as an audio-visual-based learning media in the form of animated videos for poetry learning. The research method used is qualitative. The data sources of this research are 10 poetry fragments contained in the poetry anthology